Adaptations of Migratory Birds Wintering in the East Asian–Australasian Flyway to Climate Change - Min, Joy (Technium Social Sciences Journal, 2026)
The East Asian-Australasinan Flyway (EAAF) is home to over 50 million migratory waterbirds annually, many of which rely on stopover habitats like the tidal flats in Songdo, South Korea. The rapid loss of tidal flats in the Yellow Sea region that affects carbon dioxide sinks, paired with rising global temperatures and shifting seasonal patterns, threatens these migratory birds. According to the study by Murray et al. (2018), 16 percent of the world’s tidal flats have disappeared and two-thirds of South Korea’s tidal flats have been used to expand the city. In some cases, the loss of tidal flats has created significant population declines. For example, the Great Knot’s population has suffered a 24% decline with estimates of the death of 90,000 birds, according to National Geographic (2023). Others have shown resilience to the changing climate, especially larger birds that show more resiliency by shifting migratory pathways to include fewer stopovers or relocating stopovers to less disrupted areas (Lisovski et al. 2024). Differences in migration timing have also been recorded (Damba et al. 2021). In order to protect migratory bird populations, protection and conservation efforts should be aimed at preserving a network of stopovers.